Farmer perceptions of the vulnerabilities of traditional livestock farming systems under global change - Zebensui Morales‐Reyes; Jomar M. Barbosa; José A. Sánchez‐Zapata; Irene Pérez-Ibarra (Ambio, 2025)
The continuity of traditional extensive livestock farming is being challenged by rapid socioeconomic and environmental changes, threatening livelihoods and ecosystem services critical to food security and sustainability. We conducted a large-scale assessment involving 255 livestock farmers across six extensive livestock farming systems in Spain to understand their perceptions of vulnerabilities. Using the Coupled Infrastructure Systems framework, we identified 24 different vulnerabilities, mainly caused by external socioeconomic and biophysical disturbances, such as resource costs, low profitability of livestock products, climate variability, and conflicts with wildlife. The main factors explaining these vulnerabilities were primary productivity, farm location, presence of large predators, and climatic conditions. The findings highlight the complex interplay of these factors and provide important insights for the maintenance of extensive livestock farming systems in Europe. This information is crucial for informing policy decisions aimed at supporting these farming systems and ensuring their contribution to food security, sustainability and biodiversity conservation.

The importance of locally sourced data in identifying population trends: Insights from Iberian vertebrates - Roberto C. Rodríguez-Caro; Zebensui Morales-Reyes; Alba Aguión; Rebeca Arias-Real; Eneko Arrondo; Eneko Aspillaga; Jordi Boada; Andrea Campos-Candela; Mónica Expósito-Granados; Aitor Forcada; Robin Freeman; Miguel Ángel Gómez-Serrano; et al. (Biological Conservation, 2024)

The underestimated role of carrion in vertebrates' diet studies - Esther Sebastián‐González; Jon Morant; Marcos Moleón; Daniel Redondo‐Gómez; Zebensui Morales‐Reyes; Roberto Pascual‐Rico; Juan Manuel Pérez‐García; Eneko Arrondo (Global Ecology and Biogeography, 2023)
Aim Despite the increasing scientific evidence on the importance of carrion in the ecology and evolution of many vertebrates, scavenging is still barely considered in diet studies. Here, we draw attention to how scientific literature has underestimated the role of vertebrates as scavengers, identifying the ecological traits that characterize those species whose role as scavengers could have gone especially unnoticed. Location Global. Time Period 1938–2022. Major Taxa Studied Terrestrial vertebrate scavengers. Methods We analysed and compared (a) the largest database available on scavenging patterns by carrion‐consuming vertebrates, (b) 908 diet studies about 156 scavenger species and (c) one of the most complete databases on bird and mammal diets ( Elton Traits database). For each of these 156 species, we calculated their scavenging degree (i.e. proportion of carcases where the species is detected consuming carrion) as a proxy for carrion consumption, and related their ecological traits with the probability of being identified as scavengers in diet studies and in the Elton Traits database. Results More than half of the species identified as scavengers at monitored carcasses were not assigned carrion as food source in their diet studies nor in the Elton Traits database. Using a subset of study sites, we found a direct relationship between a species' scavenging degree and its rate of carrion biomass removal. In addition, scavenger species, which were classified as non‐predators and mammals had a lower probability of being identified as scavengers in diet studies and in the Elton Traits database, respectively. Main Conclusions Our results clearly indicate an underestimation of the role of scavenging in vertebrate food webs. Given that detritus recycling is fundamental to ecosystem functioning, we encourage further recognition and investigation of the role of carrion as a food resource for vertebrates, especially for non‐predator species and mammals with higher scavenging degree .

Large-Scale Quantification and Correlates of Ungulate Carrion Production in the Anthropocene - Jon Morant; Eneko Arrondo; Ainara Cortés-Avizanda; Marcos Moleón; José A. Donázar; José A. Sánchez-Zapata; Pascual López-López; Héctor Ruiz-Villar; Iñigo Zuberogoitia; Zebensui Morales-Reyes; Lara Naves-Alegre; Esther Sebastián-González (Ecosystems, 2023)

The value of transhumance for biodiversity conservation: Vulture foraging in relation to livestock movements - Natividad Aguilera-Alcalá; Eneko Arrondo; Roberto Pascual-Rico; Zebensui Morales-Reyes; José M. Gil-Sánchez; José A. Donázar; Marcos Moleón; José A. Sánchez-Zapata (Ambio, 2022)
In recent decades, intensive techniques of livestock raising have flourished, which has largely replaced traditional farming practices such as transhumance. These changes may have affected scavengers’ behaviour and ecology, as extensive livestock is a key source of carrion. This study evaluates the spatial responses of avian scavengers to the seasonal movements of transhumant herds in south-eastern Spain. We surveyed the abundance of avian scavengers and ungulates, and analysed the factors affecting the space use by 30 GPS-tracked griffon vultures ( Gyps fulvus ). Griffons’ foraging activity increased in the pasturelands occupied by transhumant herds, which implied greater vulture abundance at the landscape level during the livestock season. In contrast, facultative scavengers were more abundant without transhumant livestock herds, and the abundance of wild ungulates did not change in relation to livestock presence. We conclude that fostering transhumance and other traditional farming systems, to the detriment of farming intensification, could favour vulture conservation.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Which bait should I use? Insights from a camera trap study in a highly diverse cerrado forest - Esther Sebastián-González; Zebensui Morales-Reyes; Lara Naves-Alegre; Carlos Javier Durá Alemañ; Leilda Gonçalves Lima; Lourival Machado Lima; José Antonio Sánchez-Zapata (European Journal of Wildlife Research, 2020)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Probing into farmers’ perceptions of a globally endangered ecosystem service provider - Marina García-Alfonso; Zebensui Morales-Reyes; Laura Gangoso; Willem Bouten; José A. Sánchez-Zapata; David Serrano; José A. Donázar (Ambio, 2019)

Shepherds’ local knowledge and scientific data on the scavenging ecosystem service: Insights for conservation - Zebensui Morales-Reyes; Berta Martín-López; Marcos Moleón; Patricia Mateo-Tomás; Pedro P. Olea; Eneko Arrondo; José A. Donázar; José A. Sánchez-Zapata (Ambio, 2019)